Innovation component of the management mechanism of a construction enterprise - Khomenko, N. (Ways to Improve Construction Efficiency, 2019)
In the article approaches to the definition of innovative potential are investigated, the mechanism of management of innovation enterprise is proposed, the predictors of its formation are determined. The given characteristics of the attributes of the innovative component of the mechanism of management of the construction enterprise, respectively, the level of riskiness; problems of financial and human resources; resistance to personnel changes.